Transformasi Pengalaman Pengunjung Melalui Perancangan UI/UX Website pada Kolam Renang Amanzi Waterpark - Frendy Wijaya; Syakirana Ciffa Khairunissa; M Doni Pranata; Anugerah Widi (Universitas Multi Data Palembang, 2026)
Amanzi Waterpark is a water-based tourism destination that attracts visitors from various age groups. However, based on direct observations and interviews with visitors, several issues were identified, including limited access to up-to-date information regarding ticket prices, promotions, operating hours, and ride details. These limitations may affect visitor convenience and interest prior to visiting the location. This study applies the User Centered Design (UCD) approach to develop a website interface that functions as an information and online ticket purchasing platform for Amanzi Waterpark. The UCD process includes understanding the context of use, identifying user requirements, designing solutions, and conducting iterative evaluations. Research subjects consisted of children, teenagers, adults, and families selected purposively. Data were collected through direct observation and interviews conducted at the research site. The result of this study is a proposed website UI/UX design that provides online ticket purchasing features, comprehensive ride information, and updated ticket prices and promotional content, aimed at improving service quality and enhancing visitor experience.